Four decades of understanding Martian geomorphology: Revisiting Baker's 'The geomorphology of Mars'. (December 2021) - Bhardwaj, Anshuman; Sam, Lydia; Gharehchahi, Saeideh
Our understanding of the Martian atmosphere, terrain and subsurface has continuously evolved over the past couple of decades as a result of a number of successful orbiter and rover missions. This prompts a need to revisit the first holistic review of Martian geomorphology, based on images from the Viking orbiters, by Victor R. Baker in 1981. Several of the interpretations and recommendations based on remote sensing in Baker's paper are as valid today as they were four decades ago. With an unprecedented focus on Mars exploration in the coming decades, it is important to revisit the advances and prospects in Martian geomorphology research.